MANAJEMEN SUMBER DAYA MANUSIA BERBASIS KOPERASI DALAM PEMBENTUKAN KARAKTER ANTIKORUPSI DI SUMATERA BARAT - ERMAN ERMAN (JEBI (Jurnal Ekonomi dan Bisnis Islam), 2016)
This study discusses the topic of human resource management based Koperasi to form an anti-corruption code. The goal is to find out how the Koperasi institutions assign roles to the management of human resources and the establishment of anti-corruption code. Method of collection, analysis, and interpretation of data using a mixed approach, which combines qualitative and quantitative approaches, refer to the version developed by John Creswell. Conclusions while (result) looked cooperatives have the potential to build human resources anticorruption character. The implication cooperative institutions elaborated the role of venture capital development organization members become strategic institutions to develop human resources and character of anticorruption in Indonesia.